Long discontinuous carbon fibre/polypropylene composites for high volume automotive applications - Burn, David T. (2016)
The volume of fibre reinforced composites is increasing within the automotive industry, as stringent emissions legislation and consumer demands for improved fuel economy are encouraging manufacturers to reduce vehicular mass. Moreover, the falling cost of carbon fibre has meant that these composites are now being considered for semi-structural and structural components for medium-volume (+50,000ppa) applications in Euro Market Segments E and F (Jaguar XF, BMW 7 Series, Mercedes S-Class).